Preparation of strontium hexaferrite magnets from celestite and blue dust by mechanochemical route - Tiwary R.K.; Narayan S.P.; Pandey O.P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In the present investigation celestite (natural ore of strontium) and blue dust (iron ore fines) have been used for the preparation of strontium hexaferrite powder. The mechanical alloying process has been adopted to prepare strontium hexaferrite powder. The celestite after chemical upradation and physically upgraded blue dust alongwith sodium carbonate was taken for the preparation of strontium hexaferrite in this experiment. The high-energy planetary ball mill with tungsten carbide jar and ball was used to prepare strontium hexaferrite powder. A long time of ball milling for different duration has led to displacement solid-state reaction. At the end of each experiment the product was washed thoroughly and dried. The X-ray diffaction study after annealing shows the development of single-phase strontium hexaferrite after 40 hrs. of milling. The resultant powder was compacted under magnetic field and sintered to prepare the magnet after annealing the ferrite powder. The magnetic properties were measured by Pulse magneto meter. The moderate value of coercivity, remanence and energy product were observed in this sintered magnet. The work illustrates the feasibility to prepare strontium hexaferrite magnetic powders directly from natural ores which can reduce the total cost of production as compared to conventional method.